Peripheral Innate Immune Activation Correlates With Disease Severity in GRN Haploinsufficiency - Ljubenkov, Peter A.; Miller, Zachary; Mumford, Paige; Zhang, Jane; Allen, Isabel Elaine; Mitic, Laura; Staffaroni, Adam; Heuer, Hilary; Rojas, Julio C.; Cobigo, Yann; Karydas, Anna; Pearlman, Rodney; et al. (Frontiers in Neurology, 2019)
Objective To investigate associations between peripheral innate immune activation and frontotemporal lobar degeneration (FTLD) in progranulin gene (GRN) haploinsufficiency. Methods In this cross-sectional study ELISA was used to measure six markers of innate immunity (sCD163, CCL18, LBP, sCD14, IL-18, and CRP) in plasma from 30 GRN mutation carriers (17 asymptomatic, 13 symptomatic) and 29 controls. Voxel based morphometry was used to model associations between marker levels and brain atrophy in mutation carriers relative to controls. Linear regression was used to model relationships between plasma marker levels with mean frontal white matter integrity (fractional anisotropy [FA]) and the FTLD modified Clinical Dementia Rating Scale sum of boxes score (FTLD-CDR SB). Results Plasma sCD163 was higher in symptomatic GRN carriers (mean 321ng/ml [SD 125]) compared to controls (mean 248ng/ml [SD 58]; p<0.05). Plasma CCL18 was higher in symptomatic GRN carriers (mean 56.9pg/ml [SD 19]) compared to controls (mean 40.5pg/ml [SD 14]; p<0.05). Elevation of plasma LBP was associated with white matter atrophy in the right frontal pole and left inferior frontal gyrus (p FWE corrected <0.05) in all mutation carriers relative to controls. Plasma LBP levels inversely correlated with bilateral frontal white matter FA (R2=0.59, p=0.009) in mutation carriers. Elevation in plasma was positively correlated with CDR-FTLD SB (b=2.27 CDR units/µg LBP/ml plasma, R2=0.76, p=0.003) in symptomatic carriers. Conclusion FTLD-GRN is associated with elevations in peripheral biomarkers of macrophage-mediated innate immunity, including sCD163 and CCL18. Clinical disease severity and white matter integrity are correlated with blood LBP, suggesting a role for peripheral immune activation in FTLD-GRN.